Predicting online safety behavior based on health belief model with internet literacy and gender as moderators - Abkooh, Elaheh Taheri (2016)
In recent times, Internet use has become an essential part of the daily lives of people worldwide. How Internet users approach the problem of Internet safety is insufficiently studied, especially in the localized context of developing nations like Malaysia. According to Cyber Security Malaysia (CSM), Malaysia is the sixth most susceptible country in the world to cyber-risks, in the form of malware attacks via computer or smart phone (The Star, 2013). In order to encourage greater safe online behavior among Malaysian Internet users, it would be essential for researchers to conduct detailed research into the problem. The aim of this study is to predict the online safety behavior of Malaysian adolescents based on Health Belief Model. This study also determines the moderating effect of internet literacy and gender as moderating on relationships between HBM factors with regard to Internet safety education program and online safety behavior among adolescents. This study employs a quantitative research design using survey method. Partial Least Squares Structural Equation modeling (PLS- SEM) method was used to assess relationships among variables. The survey was conducted in two districts in the state of Selangor (Gombak and Sepang) among students aged 14, 16 and 17 years that were in secondary schools. Stratified sampling was used to get the sample size of 400 students from 7852 student’s population in four schools, however extra questionnaires were distributed to avoid non- response bias. The criteria which were taken into considerations when choosing the sample was that the students selected should have attended the Internet safety education program. The results of this study revealed that perceived severity and perceived susceptibility,perceived benefits and self- efficacy had positive and significant effect on Internet safety behavior. Additionally, perceived barrier had negative and direct effect on Internet safety behavior among adolescent while it was showed that cues to action had no positive significant effect on Internet safety behavior. The study also found that Internet literacy fully moderated the relationships between perceived barriers and cues to action with online safety behavior among adolescent in comparison, Internet literacy had no moderating effects on the relationship between another HBM factors in Internet safety education program and online safety behavior. Moreover, gender also had no moderating effects on the relationships between HBM factors with regard to Internet safety education program and online safety behavior among adolescents.